The effectiveness of MOOCs in Technical Education: an Indian perspective - Priyanka Jarial; Himanshu Aggarwal; Bhim Sain Singla (Scientific Reports)
Abstract The analysis of user engagement in online educational courses has drawn considerable attention from researchers due to the rise of Massive Open Online Courses (MOOCs). The effectiveness of MOOCs (EMOOCs) has been identified as one of the crucial factors by numerous researchers. This led to the development of various MOOC frameworks, models, theories, designs, and principles for evaluating online learning for both students and instructors. This study uses the IBM SPSS statistical package to identify the factors contributing to the effectiveness of MOOCs (EMOOCs). It examined eight direct and indirect determinants contributing to the effectiveness of MOOCs. Data were collected from Technical courses offered at Tertiary institutions in the Punjab region, Northern India, assuming that the students already possessed knowledge of Massive Open Online Courses (MOOCs). The study revealed that the effectiveness of MOOCs (EMOOCs) is enhanced by concentrating on factors such as Course Content and Design, Performance Evaluation, Learner Feedback, Teacher-Student Interaction, and Technological Support in Massive Open Online Courses. The Discriminant Validity (HTMT ratio and Fornell-Larcker Criteria) validates the results. This study provides valuable insights into the development and implementation of Massive Open Online Courses (MOOCs) tailored to meet the specific needs of learners in Northern India, with a focus on Punjab. The research identifies key characteristics that impact the effectiveness of MOOCs, providing practical suggestions for educators and organizations seeking to enhance the learning experience in this domain.